Pengaruh The Technology Acceptance Model, Kualitas Sistem, dan Kualitas Informasi Terhadap Kepuasan Pengguna Sistem Informasi Akuntansi - Dyah Wukir Darmastuti, (2021)
This paper purpose to find out the impact of Technology Acceptance Model, Quality System, and Information Quality on Accounting Information System User satisfaction. The sample in this research is teller and customer service who works in banks, especially in South Jakarta. Sample technique used accidental sampling and total 49 samples were obtained. The data is analyzed using SPSS version 28 program and hypothesis tested using Multiple Linear Regression . The result show that the technology acceptance model, quality system, and information quality had positive significant impact on accounting information system user satisfaction.